Evaluation of the prevalence of viral bronchitis infection in broiler chicken by using ELISA Technique - N.A. Jassim; A. Ul-Jabbar M.H; N.R.Ameen; W.S.A.Alshamari; Ismael I.Hasan; B.S.Nomi (Tikrit Journal of Pure Science)
The study was conducted to evaluate the seroprevalence of Infectious Bronchitis virus (IBV) in broiler chickens farms in Kirkuk Governorate. The technique has been used in the study, Enzyme Linked Immunosorbent Assay (ELISA). Nine hundred serum samples were collected from (10) broilers farms, During the period from April 2016 to May 2016, including (90) samples from (1) symptomatic, non-vaccinated broilers farms. (90) samples from one asymptomatic, vaccinated broilers farm, and another (630) samples from one asymptomatic, non-vaccinated broilers farm, the remaining (90) samples from one symptomatic, vaccinated broilers farms, and were tested for the presence of IBV antibodies by ELISA kit. One hundred and ninety six serum samples were positive ( %65.3 ) : 78/90 (86.6%) samples were symptomatic, non-vaccinated, another 63/90 (70%) were  asymptomatic, vaccinated broilers farm, and 432/630 (68.5%) were asymptomatic, non-vaccinated broiler farm, the remaining 15/90 (16.6%) were symptomatic, vaccinated broilers farm. The remaining samples (312) were negative by  ELISA.